(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
The training process of young Greco-Roman wrestlers should be based on the widespread use of multimedia technologies, computer modeling, interactive methods, the use of which actualizes the problem of visual methods in the modern system of training and training at a new stage of scientific understanding. The use of multimedia tools is recognized as necessary and in demand in the training process of young athletes, and although they cannot and should not completely replace the coach, at the same time their use in training allows you to present the elements of the mastered technique in more detail, see your own performance errors on the screen, correlate your technique with the technique of the reference group